2022
DOI: 10.1007/s10681-022-03125-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity and selection in biofortified cassava germplasm for yield and quality root traits

Abstract: Increasing carotenoid content and improving other root quality traits has been the focus of cassava biofortification. This study aimed to (i) evaluate the genetic variability for total carotenoid content (TCC), as well as for root yield and root quality attributes; (ii) estimate potentially useful correlations for selection; and (iii) select parents for breeding and estimate the genetic gain. Data from 2011 to 2020 of 265 cassava genotypes with cream and yellow roots were analyzed for dry matter content (DMC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The dry matter content of cassava reflects its moisture content and simultaneously food, feed or industrial product yield. The dry matter content of the four cassava varieties is within the range of 14.07% and 52.67% recorded by Peprah et al [26] and De Carvalho et al [27] for some cassava varieties including yellow root cassava varieties. Higher dry matter content of the white root check (TMSI30572) in comparison to the bio-fortified varieties aligns with the previous analogous observation of Bechoff et al [41].…”
Section: Plate 1 Fresh Storage Roots Of White Root (Tmsi30572) and Th...supporting
confidence: 65%
See 1 more Smart Citation
“…The dry matter content of cassava reflects its moisture content and simultaneously food, feed or industrial product yield. The dry matter content of the four cassava varieties is within the range of 14.07% and 52.67% recorded by Peprah et al [26] and De Carvalho et al [27] for some cassava varieties including yellow root cassava varieties. Higher dry matter content of the white root check (TMSI30572) in comparison to the bio-fortified varieties aligns with the previous analogous observation of Bechoff et al [41].…”
Section: Plate 1 Fresh Storage Roots Of White Root (Tmsi30572) and Th...supporting
confidence: 65%
“…Meanwhile, there exist conflicting reports in literature on influence of biofortification of cassava on its dry matter content. Beyeneet al [25]; Bechoff et al [23]; Peprah et al [26] and De Carvalho et al [27] reported inverse relationship between dry matter and carotenoid contents of some yellow root cassava varieties. Conversely, Sánchez et al [28] and Ceballos et al [29] observed positive relationship between TCC and DMC of some bio-fortified cassava genotypes.…”
Section: Introductionmentioning
confidence: 97%
“…Beyond imparting a desirable yellow color on the roots, particularly valued in many regions of Brazil, these compounds function as potent antioxidants. Their conversion into provitamin A holds the potential to address hidden hunger arising from vitamin deficiencies, thereby contributing to the cassava biofortification initiative [27]. Notably, despite the concerted effort to prioritize accessions with elevated carotenoid levels and commendable culinary traits, this pursuit encountered challenges in the CC_Root_quality collection.…”
Section: The Formation and Diversity Of The Cassava Thematic Collectionsmentioning
confidence: 99%
“…Total carotenoid content (Ro.TCC): the concentration of total carotenoids in roots determined following the methodology outlined by [27].…”
Section: A Comprehensive Data Collection Of the Morpho-agronomic Traitsmentioning
confidence: 99%
“…Cassava (Manihot esculenta Crantz) belongs to the Euphorbiaceae family and is a root crop important for food security in many parts of the world, especially in semi-arid regions such as the Brazilian Northeast [1][2][3]. The world's production of cassava in 2022 was >330 million tons, with Nigeria showing the highest production (>60 million tons), followed by the Democratic Republic of the Congo, Thailand, Ghana, Cambodia, and Brazil [4].…”
Section: Introductionmentioning
confidence: 99%